An evaluation of the accuracy and safety of prescribing antidepressants and anxiolytics in a paediatric population. (30th November 2022) - Rizzo, D; Scott-Harris, P
Abstract: Introduction: An NHS Digital survey found that 1 in 8 children aged between 5-19 had at least one mental health disorder in England in 2017. 1 Since this survey the prescribing of antidepressants and anxiolytics has increased every year for the past five years in England. 2 A GP surgery within East Sussex requested an evaluation of whether prescribing of mental health disorder medication in paediatrics was following legal and clinical guidance. This evaluation reviewed whether the GP practice had followed Summary of Product Characteristics (SPC) prescribing requirements and the East Sussex Healthcare NHS Trust (ESHT) formulary requirements in the use of antidepressants and anxiolytics in the paediatric population. Aim: To evaluate whether medicines were prescribed in accordance with their SPC, the ESHT Formulary requirements and monitoring requirements. The evaluation also assessed whether patients' GP records were up to date as per clinic letters and whether patients were receiving cognitive behavioural therapy (CBT) and/or were under the care of appropriate mental health specialists. Methods: A search was conducted via the EMIS system. Inclusion criteria were that the patient was under the age of eighteen, had an anxiolytic and/or antidepressant prescribed and were registered with the practice between the beginning of March 2022 to the end of April 2022. Data was analysed via excel spreadsheet with patients allocated a random number. Ethics approval was not required as this was a service evaluation. Results: Eleven patients met the above criteria. Out of these patients 46% were on sertraline, 46% on fluoxetine, 18% on mirtazapine and 9% on citalopram. Audit results demonstrated that 90% of patients were under the supervision of a mental health specialist and/or receiving CBT, 66% of medications were prescribed as per their SPC with 69% prescribed in accordance with the ESHT formulary. Monitoring requirements conducted within the last 12 months was completed for 64% of patients. In addition, 45% of patients had an incorrect medication list when compared to neurology clinic letter with errors ranging from missing medication to incorrect dosing. It was also found that 82% of patients had incorrect coding on their problem lists with errors ranging from missed diagnoses to medication being incorrectly linked to problems. Discussion/Conclusion: The results show that most prescribing followed formulary and SPC requirements, and that patients had CBT either in place or in the process of being organised. However, more care is needed with monitoring, coding and processing clinic letters within this practice. Clinic letters with new diagnoses and medication changes were not seen by a clinical professional, potentially leading to errors. A small cohort of patients and COVID restrictions with staff and patients were the primary limitations of this study. More research is needed to determine whether other GP surgeries have the same strengths and challenges found within this surgery, and whether lessons can be learnt to standardise practice. References: 1. NHS Digital. Mental health of children and young people in England, 2017. Available from: https://dera.ioe.ac.uk/32622/1/MHCYP%202017%20Summary.pdf 2. NHS Business Services Authority. Medicines Used in Mental Health – England – 2015/16 to 2020/21. Available from: https://www.nhsbsa.nhs.uk/statistical-collections/medicines-used-mental-health-england/medicines-used-mental-health-england-201516-202021